Estudos hematológicos e caracterização estrutural e funcional das hemoglobinas do peixe pulmonado Lepidosiren paradoxa (Dipnoi, Fitzinger, 1837) e do peixe de respiração aérea facultativa Hoplerythrinus unitaeniatus (Characiformes, Spix, 1829) - Silva, Hugo Ribeiro da (2011)
The blood cell composition in their qualitative and quantitative aspects as well as the functional properties of hemoglobin (Hb) shows characteristic of adaptation to the aquatic environment, aiding the understanding of the adaptability of the fish to the environment. The present study aimed to analyze the peripheral blood cells and the structural and functional characterization (in vitro) of hemoglobins of the South American lungfish, Lepidosiren paradoxa and facultative air-breathing fish H. unitaeniatus collected nearby Cuiaba, MT. The hematological variables, blood cell size, plasma ions, glucose and protein concentrations and the osmolality as well as the electrophoretic patterns of Hbs, the Root effect, quantification and the effect of allosteric modulators (IHP, ATP, GTP, 2.3 - BPG and NaCl) of the affinity of Hb to oxygen and Hb affinity in experiments of oxygenation in the blood stripped to and 4oC, 21oC and 40oC. The blood cells of L. paradoxa are exceptionally large and not numerous compared to H. unitaeniatus. The hematocrit and blood pH were similar in the two species. The erythrocyte number was lower in L. paradoxa (52 .103 ± 17 L-1) than in H unitaeniatus (2386 .103 ± 370 L-1). The hematimetric indexes mean corpuscular volume and mean corpuscular Hb were higher in L. paradoxa while the mean corpuscular Hb concentration and Hb concentration were higher in H. unitaeniatus. Among the white blood cells, in L. paradoxa, the lymphocytes (65.00 ± 4.00 %) were the most frequent cells, followed by eosinophils (19.00 ± 3.00 %), neutrophils (12.00 ± 2.00 %), monocytes (2.00 ± 0.60 %) and basophils (1.40 ± 0.40 %). In H. unitaeniatus lymphocytes were also the most frequent cells (85.14 ± 3.21 %) followed by neutrophils (12.00 ± 3.00 %) and monocytes (2.90 ± 1.23 %). In L. paradoxa the Mg+2, glucose and total protein plasma levels were significantly smaller than in H. unitaeniatus. There were no significant differences in the levels of K+, Ca+2, Cl- and osmolarity of plasma and between both species. Two Hb components, one major and another minor band was identified in L. paradoxa and another smaller; in H. unitaeniatus 6 anode components being 3 slow components and 3 fast component have been identified at different concentrations. In both species the stripped Hbs in three temperatures and in the presence of modulators, showed normal Bohr effect. In L. paradoxa cooperatively values were near 2.00 indicating cooperatively and absence of effect of Root; in H. unitaeniatus the cooperatively values were near 1.50, indicating low cooperatively and presence of Root effect. The affinity of Hb-oxygen proved be higher as decreased the temperature. The 2.3 - BPG was little effective in modulate the Hb in both species. The IHP ATP, GTP, and NaCl acted as negative modulators, being more effective in the modulation of Hb of H. unitaeniatus. The 2.3 - BPG was not detected in H. unitaeniatus and the ATP was the primary nucleotide intraeritrocitário for the two species being approximately 2 times higher than the GTP. In L. paradoxa was detected small amount IP2, but not in H. unitaeniatus. Our results show marked differences between the blood cells of L. paradoxa and H. unitaeniatus and the ability of adaptation of Hbs to environmental conditions to which they living.